2008
DOI: 10.1098/rsbl.2008.0233
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian malformations and inbreeding

Abstract: Inbreeding may lead to morphological malformations in a wide variety of taxa. We used genetic markers to evaluate whether malformed urodeles were more inbred and/or had less genetic diversity than normal salamanders. We captured 687 adult and 1259 larval tiger salamanders (Ambystoma tigrinum tigrinum), assessed each individual for gross malformations, and surveyed genetic variation among malformed and normal individuals using both cytoplasmic and nuclear markers. The most common malformations in both adults an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
2
18
2
3
Order By: Relevance
“…If only limited variance exists in the level of inbreeding among individuals, for example because the entire population is either highly inbred or highly outbred, then no correlation is expected [98,118]. This could perhaps explain why no GFCs were detected in studies of large healthy populations of A. tigrinum [114], B. calamita and R. temporaria [119] in contrast to studies that compared individuals from relatively inbred and outbred populations (e.g., 51,116]). On the other hand, the latter approach has been criticised because environmental heterogeneity over the geographic range sampled can potentially create spurious relationships [120].…”
Section: Limitationscontrasting
confidence: 45%
See 1 more Smart Citation
“…If only limited variance exists in the level of inbreeding among individuals, for example because the entire population is either highly inbred or highly outbred, then no correlation is expected [98,118]. This could perhaps explain why no GFCs were detected in studies of large healthy populations of A. tigrinum [114], B. calamita and R. temporaria [119] in contrast to studies that compared individuals from relatively inbred and outbred populations (e.g., 51,116]). On the other hand, the latter approach has been criticised because environmental heterogeneity over the geographic range sampled can potentially create spurious relationships [120].…”
Section: Limitationscontrasting
confidence: 45%
“…In an allozyme survey of British Bufo bufo populations, Hitchings and Beebee [109] documented a correlation between low genetic diversity and physical abnormalities in small isolated populations found in urban environments. Similar effects have been observed in Rana sylvatica [15] and Rana temporaria [65], although the failure to document any correlation between malformations and individual heterozygosity within a population of Ambystoma tigrinum [114] confirms that other factors are also responsible for amphibian deformity. Indeed, physical abnormalities may arise due to a variety of factors, and investigating GFCs in this context without considering other biotic and abiotic factors, could prove misleading.…”
Section: Measures Of Fitnessmentioning
confidence: 54%
“…This is a particularly difficult quantity to investigate explicitly, as it requires estimates of the extent of inbreeding in different individuals as well as measures of fitness. While some studies in amphibians have found correlations between degree of inbreeding and fitness (Halverson et al 2006), others have not found such evidence (Williams et al 2008). One interesting corollary to this in r-selected amphibians is that natural selection can act strongly on eggs or larvae to reduce the observed amount of inbreeding in the metamorphosing population, a pattern that could be missed if sampling only eggs or larvae.…”
Section: Methods and Their Applications To Amphibiansmentioning
confidence: 96%
“…see Fig. 1(a) in Williams et al, 2008). Another individual of L. bo scai, sampled in June 2012, presented abnormally short digits (brachydactyly).…”
Section: Amphibian Deformities In North-central Portugalmentioning
confidence: 99%
“…ManouvrierHanu et al, 1999;Hill Lettice, 2013). Notwithstanding, natural mutation rates or inbreeding do not seem plausible explanations when high frequencies of abnormality are observed for multiple species, and across broad geographic range (Blaustein Johnson, 2003;Williams et al, 2008). Instead, biotic interactions and environmental factors are often highlighted as the cause.…”
mentioning
confidence: 99%